NUTRACEUTICAL POTENTIAL OF VERMICELLI PREPARED BY GLUTEN-FREE COMPOSITE FLOUR - AGARWAL, SRISHTI; CHAUHAN, EKTA SINGH (International Journal of Current Pharmaceutical Research, 2022)
Objective: Nutritional, phytochemical and antioxidant properties of all ratios of gluten free composite flour-based Vermicelli was evaluated in this study. The blend of proso millet flour (PF), adzuki bean flour (AF) and basil seeds flour (BF) was used in composite flour. Methods: The variations of three composite flours were prepared as, A being (PF: AF: BF=50:45:5), B being (PF: AF: BF=60:35:5) and C being (PF: AF: BF=70:25:5), respectively. The macronutrients like moisture, ash, fat, fiber, protein and carbohydrate were assessed in this study. Minerals such as calcium, iron, phosphorus and zinc were analyzed in micronutrients. Results: The result of macronutrient and micronutrient of a ratio were moisture (5.2±0.1), ash (2.1±0.2), protein (13.0±0.0), fat (1.6±0.0), fiber (3.0±0.0) and carbohydrate (60.0±0.2g/100g) respectively. Calcium (150.0±0.3), iron (3.5±0.1), zinc (2.0±0.3) and phosphorus (250.6±0.6 mg/100g) were also there in gluten-free Pasta. The current study revealed that various macro and micronutrients were present in gluten-free Vermicelli. In the prepared products, flavonoids, saponins, tannin, glycocides, alkaloids and steroids are the few phytochemicals present. The study results also show that gluten-free Vermicelli has good antioxidant activity. In the A ratio, overall, all nutrients are found. It was found by the sensory evaluation Vermicelli on a 9 point hedonic scale that A ratio was more acceptable than the B and C ratio. Conclusion: Therefore, it can be useful for celiac diseases as well as patients suffering from diseases like hypertension, anemia and diabetes.